THE COPROCESSED OF MANNITOL-CALCIUM CARBONATE BY SPRAY DRYING AND WET GRANULATION METHODS AS EXCIPIENT IN TABLET - Anggraeni, Wulan
Background and Purpose : The coprocessed is a technique to improve the function of excipients such as compactibüity and flowability. The calcium carbonate is used as an alkaline diluent that can increase solubility and dissolution of drugs and also uses in formulas of tablets effervescent, chawable and calcitm supplement> but it's compactibility is poor. The mannitol is plastis and reported can improved the hardness of tablet and compactibility„ The aim of this research was to increase the functionality of calcium carbonate by mixing with mannitol made by spray drying and wet granulation. Methods The coprocessed mannitol-calcium carbonate was made with drying (SD-MC) and wet granulation (GB-MC) at ratio of 8020; 6040; 40:60; and 20180. The determination of parameters of spray drying process used a mannitot solution of 4%, 8% and 12%, the inlet temperature 900C or 1 ITC, feed rate, air pressure